2020
DOI: 10.32584/jikmb.v3i1.253
|View full text |Cite
|
Sign up to set email alerts
|

Efektifitas Edukasi Kesehatan Menggunakan Media Booklet terhadap Self Care Management Pasien Penyakit Ginjal Kronik di Unit Hemodialisa

Abstract: Pasien penyakit ginjal kronik membutuhkan kemampuan dalam melakukan perawatan pada dirinya sendiri. Kemampuan self care perlu ditingkatkan dengan membekali pengetahuan pasien sehingga kualitas hidupnya meningkat. Salah satu upaya untuk meningkatkan pengetahuan pasien dapat dilakukan dengan memberikan pendidikan kesehatan dengan menggunakan media booklet. Penelitian ini bertujuan untuk mengetahui efektifitas edukasi dengan menggunakan media booklet terhadap self care managementpasien penyakit ginjal kronik di u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
0
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 2 publications
1
0
0
4
Order By: Relevance
“…It can be concluded that hypertension education using booklet media is effective in changing hypertension selfmanagement behavior in hypertensive patients (Herwanti et al, 2021). This is in line with other research which found a significant effect of providing health education about self-care for chronic kidney disease using booklet media on self-care management in patients undergoing hemodialysis at Kraton Hospital, Pekalongan Regency (ρ=0.000) (Prastiwi et al, 2020). Research from Cumayunaro et al, (2020) obtained the same results, namely that there were significant differences in mothers' knowledge and attitudes towards early detection of children's growth and development before and after being given health education.…”
Section: The Characteristicssupporting
confidence: 91%
“…It can be concluded that hypertension education using booklet media is effective in changing hypertension selfmanagement behavior in hypertensive patients (Herwanti et al, 2021). This is in line with other research which found a significant effect of providing health education about self-care for chronic kidney disease using booklet media on self-care management in patients undergoing hemodialysis at Kraton Hospital, Pekalongan Regency (ρ=0.000) (Prastiwi et al, 2020). Research from Cumayunaro et al, (2020) obtained the same results, namely that there were significant differences in mothers' knowledge and attitudes towards early detection of children's growth and development before and after being given health education.…”
Section: The Characteristicssupporting
confidence: 91%
“…Hasil penelitian kami juga memaparkan sebagian besar responden merasa tidak memerlukan informasi tambahan mengenai penyakit dan diitnya. Sama dengan penelitian sebelumnya setelah pasien diberikan edukasi kesehatan tentang penyakitnya hasilnya menunjukkan pemahaman yang baik tentang penyakit dan kepatuhan dalam manajemen keperawatan diri dirumah (Prastiwi, Sukmarini, & Isrofah, 2020) (Friedman, Bowden, & Jones, 2014).…”
Section: Pendahuluanunclassified
“…Penelitian menunjukkan bahwa pengetahuan mengenai self-management dapat meningkatkan kepercayaan diri, efikasi diri serta kepatuhan pasien-pasien dengan CKD dalam mengelola penyakitnya secara mandiri [13,23]. Setelah satu minggu keluar dari rumah sakit, terjadi peningkatan skor self-management dari 53 menjadi 67 walaupun masih dalam kategori yang sama yakni partly compensatory system.…”
Section: Hasil Dan Pembahasanunclassified